Effects of cellulose concentrations on the syntrophic interactions between Clostridium cellulovorans 743B and Rhodopseudomonas palustris CGA009 in coculture fermentation for biohydrogen production. (21st September 2015) - Lu, Hongyuan; Lee, Patrick K.H.
Abstract The integration of dark and photo fermentation is a promising strategy to enhance biohydrogen productivity and substrate utilization, and therefore can be adopted to advance the development of industrial biohydrogen production. However, the mutualistic interactions between dark fermentative and purple non-sulfur photosynthetic microorganisms remain poorly understood due to the challenges of incorporating two physiologically different bacteria in one integrated fermentation system. In this work, an experimentally and genetically tractable model combining the cellulose-degrading bacterium Clostridium cellulovorans 743B and photosynthetic bacterium Rhodopseudomonas palustris CGA009 was successfully established. The responses of this coculture system to different cellulose concentrations were characterized. At all four levels of initial cellulose concentrations (2, 3, 4 or 5 g/L), the hydrogen productivity and cellulose degradation of cocultures were all significantly enhanced to varying extents in comparison to monocultures. The mechanism of the beneficial interaction was due to consumption of volatile fatty acids by R. palustris, which in turn balanced the pH to increase cellulose consumption by C. cellulovorans. Overall, the results demonstrated that the mutualism between C. cellulovorans and R. palustris could lead to a more efficient biohydrogen production process, thus making the pairing of these two strains a suitable model for further study on syntrophic interactions.